2013
DOI: 10.1016/j.phytochem.2013.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Leishmanicidal activity of Cecropia pachystachya flavonoids: Arginase inhibition and altered mitochondrial DNA arrangement

Abstract: The plant Cecropia pachystachya Trécul is widely used in Brazilian ethnomedicine to treat hypertension, asthma, and diabetes. Arginase is an enzyme with levels that are elevated in these disorders, and it is central to Leishmania polyamine biosynthesis. The aims of this study were to evaluate antileishmanial activity and inhibition of the arginase enzyme by C. pachystachya extracts, and to study changes in cellular organization using electron microscopy. The ethanol extract of C. pachystachya was tested on Lei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 55 publications
(66 reference statements)
0
40
0
2
Order By: Relevance
“…Cruz et al (52) demonstrated that flavonoids, in addition to altering the arrangement of mitochondrial deoxyribonucleic acid (DNA), also inhibit the enzyme arginase, which participates in the parasite's polyamine biosynthesis. Fonseca-Silva et al (53) demonstrated that treatment of L. amazonensis with quercetin, a flavonoid most commonly found in plants, increases the production of reactive oxygen species (ROS), promotes mitochondrial dysfunction in the parasite, and inhibits cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…Cruz et al (52) demonstrated that flavonoids, in addition to altering the arrangement of mitochondrial deoxyribonucleic acid (DNA), also inhibit the enzyme arginase, which participates in the parasite's polyamine biosynthesis. Fonseca-Silva et al (53) demonstrated that treatment of L. amazonensis with quercetin, a flavonoid most commonly found in plants, increases the production of reactive oxygen species (ROS), promotes mitochondrial dysfunction in the parasite, and inhibits cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…The profile of the constituents from Cecropia pachysatachya FCP extract was performed using liquid chromatography-mass spectra (LC-MS) using Esquire 3000 Plus (Bruker Daltonics) as described previously (Cruz et al, 2013).…”
Section: Characterization Of the Active Constituents From C Pachystamentioning
confidence: 99%
“…These studies have indicated a phenolic‐rich profile, which includes C ‐glycosylated flavonoids, such as orientin, isoorientin, vitexin and isovitexin, in addition to chlorogenic acid. These constituents have been related to biological properties, such as anti‐inflammatory, leishmanicidal, and hypoglycemic activities, among others . Cecropia hololeuca possesses silver leaves, and because of this, is popularly known in Brazil as silver embaúba .…”
Section: Introductionmentioning
confidence: 99%